Using Power BI to Apply Business Intelligence to Product Sales - Sinambela, Annabella Dian Dameria; Zahra, Almira; Jaman, Jajam Khaerul (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This research aims to investigate the use of Power BI, which is one of the leading tools in the BI industry, in applying Business Intelligence in the context of product sales. Business Intelligence (BI) is a solution used to address the needs of companies with a focus on data analysis and access to support better decision making. The main goal is to help companies in the decision-making process through steps such as designing databases, Data Warehouse, and report generation. The result of this research is the analysis of reports showing product sales with the lowest contribution compared to other areas. Therefore, products that have the lowest contribution need special attention. One of the efforts that can be made is to carry out promotions and provide discounts to increase the number of orders from customers in a wider area.